Congenital duodenal obstruction due to duodenal atresia with preduodenal portal vein, annular pancreas, and intestinal malrotation associated with situs inversus abdominis: A case report - Samuel Wabada; Auwal Mohammed Abubakar; Bello Mustapha; Simon Pius; Jibril Khalil; Abdulmalik Kabu Abana (Elsevier, 2015)
The operations for congenital duodenal obstruction due to duodenal atresia with, annular pancreas still present a unique challenge. Of the operative techniques mentioned in the literature duodenoduodenostomy was the most frequently performed, however peculiar situations may arise that may warrant gastrojejunostomy. We report a case of duodenal obstruction due to duodenal atresia with preduodenal portal vein, and annular pancreas, co-existing with intestinal malrotation, a right sided stomach and spleen in which, the patient had gastrojejunostomy.